2007
DOI: 10.1523/jneurosci.4308-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Control of Grasping Actions: Object-Specific Motor Facilitation Requires Sustained Visual Input

Abstract: Dorsal stream visual processing is generally considered to underlie visually driven action, but when subjects grasp an object from memory, as visual information is not available, ventral stream characteristics emerge. In this study we use paired-pulse transcranial magnetic stimulation (TMS) to investigate the importance of the current visual input during visuomotor grasp. Previously, the amplitude of the paired-pulse motor evoked potentials (MEPs) in hand muscles before movement onset have been shown to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
5
23
0
Order By: Relevance
“…Our results are consistent with observations from previous studies suggesting that excitatory inputs to M1 are modulated during motor preparation [23,24]. Those studies indicated that there were object-and musclespecific changes in the cortical excitability of M1 immediately before a participant grasped an object.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with observations from previous studies suggesting that excitatory inputs to M1 are modulated during motor preparation [23,24]. Those studies indicated that there were object-and musclespecific changes in the cortical excitability of M1 immediately before a participant grasped an object.…”
Section: Discussionsupporting
confidence: 93%
“…context or task dependent) [17,22]. Like single-pulse TMS, pairedpulse TMS has been shown to be a sensitive method to measure cortico-cortical interactions, and has been used successfully in experiments assessing the excitability of circuits intrinsic to the cerebral cortex itself [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M1 receives two major inputs. [41][42][43] One is from the supplementary motor cortex (SMA) and presupplementary motor cortex (preSMA), which in turn receives inputs from the basal ganglia and prefrontal cortex. This circuit is mainly involved in decisionmaking movement.…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…Modulation of sensory experience appears to influence performance of healthy humans [132], some patients [76], and the aging [133], and when sensory modulation is a benefit above real world experiences [134]. Visual experience of real objects engages important neural regions involved with recognition of the objects, properties, and location in space, and provides for online correction of movement [23,101,[135][136][137][138]. Postural, visual, tactile, and other sensory experiences modulate sensory fields important for responding accurately to stimuli, and inform the nervous system of body position in peripersonal space relevant when moving about and interacting with real world objects [26,83,127,132].…”
Section: Modulation Of Multi-sensory Experiencementioning
confidence: 99%